Layered ceramic electronic component and manufacturing method for the same
By using the combination of large-particle and small-particle-sized ceramic particles in the dielectric layer of the multi-layer ceramic capacitor, the problems of surface smoothness and voltage resistance characteristics caused by uneven particle size are solved, and higher reliability and thinner capacitors are achieved.
Patent Information
- Application Number
- JP2023171380
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-02
- Publication Date
- 2025-04-14
AI Technical Summary
In multi-layer ceramic capacitors, uneven particle sizes of the ceramic particles cause a decrease in smoothness of the surface of the dielectric layer, which in turn affects the voltage resistance characteristics and the reliability of the components.
The combination of large-particle size and small-particle size ceramic particles is used to ensure that the particle size of large-particle size ceramic particles exceeds half of the average thickness of the dielectric layer, while the particle size of small-particle size ceramic particles is one-quarter of the large-particle size. This particle size distribution is used to fill the gaps between large-particle size particles and improve the smoothness of the dielectric layer.
Through this particle size distribution design, the voltage resistance characteristics and reliability of the multilayer ceramic capacitor can be significantly improved, while making the capacitor thinner.
Smart Images

Figure 2025062368000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a multilayer ceramic electronic component and a method for manufacturing the same. [Background technology]
[0002] For example, as multilayer ceramic electronic components such as multilayer ceramic capacitors become thinner, it is believed that the grain size in the lamination direction of the ceramic particles constituting the dielectric layers will essentially become the thickness of the dielectric layers (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2002-305124 A Summary of the Invention [Problem to be solved by the invention]
[0004] In the above case, the smoothness of the surface of the dielectric layer is impaired due to the variation in the particle size of the ceramic particles, which may deteriorate the voltage resistance characteristics and reduce the reliability of the multilayer ceramic electronic component.
[0005] SUMMARY OF THE PRESENT DISCLOSURE ... In view of the above problems, it is an object of the present invention to provide a thin-layer multilayer ceramic electronic component capable of improving reliability, and a method for manufacturing the same. [Means for solving the problem]
[0006] The multilayer ceramic electronic component of the present invention has a laminate in which dielectric layers and internal electrode layers are alternately laminated, the dielectric layers contain a plurality of large-diameter ceramic particles having a particle size larger than half the average thickness of the dielectric layers, and a greater number of small-diameter ceramic particles than the large-diameter ceramic particles, and the particle size of the small-diameter ceramic particles is 0.25 times or less the maximum particle size of the large-diameter ceramic particles.
[0007] In the above-mentioned monolithic ceramic electronic component, the small-diameter ceramic particles may have a diameter not greater than 0.2 times the maximum diameter of the large-diameter ceramic particles.
[0008] With regard to the above-described multilayer ceramic electronic component, in a cross section of the dielectric layer along a stacking direction of the laminate, the particle size of the small-diameter ceramic particles that is most abundant on a line that divides the dielectric layer into two at approximately the center in the stacking direction may be one-third or less of the particle size of the large-diameter ceramic particles that is most abundant on the line.
[0009] In the above-mentioned multilayer ceramic electronic component, the large-diameter ceramic grains may be in contact with the internal electrode layers.
[0010] In the above-described multilayer ceramic electronic component, when the maximum particle size of the large-diameter ceramic particles and the small-diameter ceramic particles distributed on a line that divides the dielectric layer in half in the cross section at approximately the center in the stacking direction is defined as Ra, and the maximum particle size of the large-diameter ceramic particles and the small-diameter ceramic particles distributed on a line that divides the dielectric layer in half in the stacking direction at a position away from the interface with the internal electrode layer by a distance 0.1 times the average thickness of the dielectric layer in the stacking direction is defined as Rb, 0.1≦Rb / Ra≦0.8 may be satisfied.
[0011] In the above-mentioned monolithic ceramic electronic component, the dielectric layers may have an average thickness of 0.2 to 0.4 μm.
[0012] In the above-mentioned monolithic ceramic electronic component, the ratio of the average thickness of the internal electrode layers to the average thickness of the dielectric layers may be greater than 0.5 and smaller than 1.0.
[0013] The method for producing a multilayer ceramic electronic component of the present invention includes the steps of: forming a green sheet from a slurry containing a large-diameter ceramic powder and a small-diameter ceramic powder having an average particle size that is 0.25 times or less the maximum particle size of the large-diameter ceramic powder; forming a first internal electrode pattern on the green sheet; stacking and pressing a plurality of the green sheets; dividing the pressed green sheets into a plurality of laminates along the stacking direction; and firing the laminates, wherein in the green sheet forming step, the green sheet is formed to have a thickness that is less than twice the average particle size of the large-diameter ceramic powder.
[0014] In the above manufacturing process, the small diameter ceramic powder may have an average particle size that is 0.2 times or less the average particle size of the large diameter ceramic powder.
[0015] In the above manufacturing process, the slurry may contain 4 to 8 times as many particles of the small diameter ceramic powder as the large diameter ceramic powder. Effect of the Invention
[0016] According to the present invention, it is possible to reduce the thickness of a multilayer ceramic electronic component and improve its reliability. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a perspective view showing an example of a multilayer ceramic capacitor. [Diagram 2] FIG. 2 is a cross-sectional view of the multilayer ceramic capacitor taken along line AA in FIG. [Diagram 3] FIG. 3 is a cross-sectional view of the multilayer ceramic capacitor taken along line BB in FIG. [Figure 4] FIG. 4 is a cross-sectional view of the multilayer ceramic capacitor taken along line CC in FIG. [Diagram 5] FIG. 5 is an example of an enlarged cross-sectional view of a dielectric layer and an internal electrode layer. [Figure 6]FIG. 6 is a diagram showing an example of the particle size distribution of large and small ceramic particles present on the center line. [Figure 7] FIG. 7 is a flowchart showing an example of a manufacturing process for a multilayer ceramic capacitor. [Figure 8] FIG. 8 is a cross-sectional view showing the process from the green sheet formation step to the lamination and compression bonding step. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] [Embodiment] (Structure of multilayer ceramic capacitors) Fig. 1 is a perspective view showing an example of a multilayer ceramic capacitor 1. Fig. 2 is a cross-sectional view of the multilayer ceramic capacitor 1 taken along line AA in Fig. 1. Fig. 3 is a cross-sectional view of the multilayer ceramic capacitor 1 taken along line BB in Fig. 2. Fig. 4 is a cross-sectional view of the multilayer ceramic capacitor 1 taken along line CC in Fig. 2.
[0019] The multilayer ceramic capacitor 1 has a laminate 2 having a substantially rectangular parallelepiped shape, and external electrodes 3a, 3b provided on a pair of opposing end faces 2A, 2B of the laminate 2. The multilayer ceramic capacitor 1 is an example of a multilayer ceramic electronic component. Other examples of multilayer ceramic electronic components include a multilayer ceramic varistor and a multilayer ceramic thermistor, and in this embodiment, the multilayer ceramic capacitor 1 is used as a representative example of these.
[0020] 1 to 4 show mutually orthogonal X, Y, and Z directions. The X direction is the length (L) direction of the multilayer ceramic capacitor 1, and coincides with the direction in which a pair of end faces 2A, 2B of the laminate 2 face each other. The Y direction is the width (W) direction of the multilayer ceramic capacitor 1, and coincides with the direction in which a pair of side faces 2E, 2F of the laminate 2 face each other. The Z direction is the height (T) direction of the multilayer ceramic capacitor 1, and coincides with the direction in which the upper face 2C and the lower face 2D of the laminate 2 face each other and the lamination direction of the laminate 2. The length direction is an example of a direction approximately orthogonal to the lamination direction of the laminate 2, and the end faces 2A, 2B face the length direction.
[0021] The laminate 2 has an upper surface 2C, a lower surface 2D, a pair of end surfaces 2A, 2B, and a pair of side surfaces 2E, 2F. The upper surface 2C and the lower surface 2D are approximately flat surfaces facing each other in the stacking direction, the pair of end surfaces 2A, 2B are approximately flat surfaces facing each other in the length direction, and the pair of side surfaces 2E, 2F are approximately flat surfaces facing each other in the width direction.
[0022] The laminate 2 has a laminated structure in which dielectric layers 22, mainly composed of a ceramic material that functions as a dielectric, and internal electrode layers 23 are alternately laminated, and further a pair of cover layers 20, 21 are laminated so as to sandwich the dielectric layers 22 and the internal electrode layers 23 from both sides in the lamination direction. In the laminate 2, the portion sandwiched between a pair of internal electrode layers 23 adjacent to each dielectric layer 22 contributes to the electrostatic capacitance of the multilayer ceramic capacitor 1, and is sometimes called a "capacitive layer."
[0023] The cover layers 20 and 21 sandwich the capacitive layer from both sides in the stacking direction. Edge portions 200 and 210 having curved surfaces are formed on both ends of the cover layers 20 and 21 in the longitudinal direction, respectively.
[0024] The laminate 2 is also provided with side margins 40, 41 which form the respective side surfaces 2E, 2F. The side margins 40, 41 extend along the length direction and sandwich the laminated region of the internal electrode layers 23 and the dielectric layers 22, i.e., the capacitive layers, from both sides in the width direction. The side margins 40, 41 are mainly composed of the same ceramic material as the dielectric layers 22.
[0025] The internal electrode layers 23 have a generally rectangular shape when viewed from the front in the stacking direction, and face each other in the stacking direction across the dielectric layer 22. One end of the internal electrode layers 23 is alternately extended to the end faces 2A, 2B along the stacking direction and connected to the external electrodes 3a, 3b.
[0026] The dielectric layer 22 may be, for example, a compound represented by the general formula ABO 3 The main phase of the ceramic material is a perovskite structure represented by the formula: 3-α (α indicates a small number). For example, the ceramic material is BaTiO 3 (Barium titanate), CaZrO 3 (Calcium Zirconate), CaTiO 3 (Calcium titanate), SrTiO 3 (Strontium titanate), MgTiO 3 (Magnesium titanate), which forms a perovskite structure 1-x-y Ca x Sr y Ti 1-z Zr z O 3 (0≦x≦1, 0≦y≦1, 0≦z≦1) and the like. 1-x-y Ca x Sr y Ti 1-z Zr z O 3 Examples include barium strontium titanate, barium calcium titanate, barium zirconate, barium titanate zirconate, calcium titanate zirconate, and barium calcium titanate zirconate.
[0027] The internal electrode layers 23 are mainly composed of base metals such as Ni (nickel), Cu (copper), Sn (tin), etc. The internal electrode layers 23 may be made of precious metals such as Pt (platinum), Pd (palladium), Ag (silver), Au (gold), etc., or alloys containing these metals.
[0028] The external electrodes 3a, 3b cover the end faces 2A, 2B of the laminate 2 that face each other in the longitudinal direction of the multilayer ceramic capacitor 1. The external electrodes 3a, 3b extend onto the upper face 2C, the lower face 2D, and the side faces 2E, 2F. However, the external electrodes 3a, 3b are spaced apart from each other on the surfaces of the upper face 2C, the lower face 2D, and the side faces 2E, 2F.
[0029] The main components of the external electrodes 3a and 3b include metals such as Ni (nickel) and Cu (copper), etc. The external electrodes 3a and 3b may also include one or more plating films whose main components are metals such as Ni (nickel) and Sn (tin).
[0030] (Microstructure of the dielectric layer) Fig. 5 is an example of an enlarged cross-sectional view of the dielectric layer 22 and the internal electrode layers 23u, 23d. Fig. 5 shows the microstructure of a part of the dielectric layer 22 in Fig. 2, and the internal electrode layers 23 (23u, 23d) adjacent to the dielectric layer 22 above and below in the stacking direction. Note that, in this example, the microstructure of the dielectric layer 22 in a cross section along the stacking direction and length direction of the laminate 2 is shown, but a similar microstructure also exists in a cross section along the stacking direction and width direction of the laminate 2 as shown in Fig. 3.
[0031] The dielectric layer 22 includes large-diameter ceramic particles 220a and small-diameter ceramic particles 220b. The large-diameter ceramic particles 220a have a grain size Rt that is greater than half the average thickness D of the dielectric layer 22. The grain size Rt of the large-diameter ceramic particles 220a is, for example, the maximum dimension in the stacking direction. Therefore, the large-diameter ceramic particles 220a are randomly arranged on the XY plane, i.e., on the surfaces of the internal electrode layers 23u and 23d, without forming any substantial steps in the stacking direction.
[0032] The particle size of the small diameter ceramic particles 220b is 0.25 times or less the maximum particle size of the large diameter ceramic particles 220a. Therefore, the maximum particle size of the small diameter ceramic particles 220b is ¼ of the average thickness D of the dielectric layer 22. As a result, even if the particle sizes of the large diameter ceramic particles 220a vary, the small diameter ceramic particles 220b fill the gaps around the large diameter ceramic particles 220a and act to reduce the unevenness of the surface of the dielectric layer 22, so that the surface of the dielectric layer 22 in contact with the internal electrode layers 23u, 23d is smoothed.
[0033] This suppresses short-circuiting between the internal electrode layers 23u, 23d and protrusion of the internal electrode layers 23u, 23d into the dielectric layer 22. This improves the withstand voltage characteristics of the dielectric layer 22, and improves the reliability of the multilayer ceramic capacitor 1.
[0034] Preferably, the particle size of the small diameter ceramic particles 220b may be 0.2 times or less the maximum particle size of the large diameter ceramic particles 220a. In this case, the irregularities on the surface of the dielectric layer 22 can be further reduced, so that the surface of the dielectric layer 22 is more effectively smoothed.
[0035] Furthermore, it is preferable that the average thickness D of the dielectric layer 22 is 0.2 to 0.4 (μm), since it is easy to match the particle size in the stacking direction of the large-diameter ceramic particles 220a, the smoothing is more effective, and the voltage resistance characteristics are improved. Here, the average thickness D of the dielectric layer 22 is the distance between line segments Eu, Ed drawn along a position where the coordinates of a plurality of points on each surface of the dielectric layer 22 are sampled at regular intervals in a cross-sectional photograph of the laminate 2 taken with, for example, a SEM (Scanning Electron Microscope), and the coordinates (Z coordinates) in the stacking direction of each sampling point are averaged.
[0036] Furthermore, when the average thickness D of the dielectric layer 22 is 0.2 to 0.4 (μm), the ratio of the average thickness d of the internal electrode layers 23u, 23d to the average thickness D of the dielectric layer 22 is preferably greater than 0.5 and smaller than 1.0, because the thickness of the internal electrode layers 23u, 23d can be thinned to a degree that can appropriately relieve stress and can be made large enough to ensure a coexistent material amount that can suppress crack generation. Here, the average thickness d of the internal electrode layers 23u, 23d is the distance between the line segment Li drawn along the position where the coordinates of multiple points on the surface of the internal electrode layers 23u, 23d are sampled at regular intervals in a cross-sectional photograph of an SEM, for example, and the line segments Eu, Ed on the surface of the dielectric layer 22. Note that FIG. 5 shows only the average thickness d of the internal electrode layer 23u.
[0037] Moreover, the center line Lm divides the dielectric layer 22 into two at approximately the center in the stacking direction in a cross section of the dielectric layer 22 along the stacking direction of the laminate 2. Specifically, the center line is set at a distance of D / 2 from the line segments Eu and Ed.
[0038] Moreover, the upper end line Lu divides the dielectric layer 22 into two at a position in the stacking direction away from the interface with the internal electrode layer 23u by a distance of 0.1 times the average thickness D of the dielectric layer 22. The interface between the dielectric layer 22 and the internal electrode layer 23u is considered to be substantially along the line segment Eu.
[0039] The bottom line Ld also divides the dielectric layer 22 into two at a position in the stacking direction away from the interface with the internal electrode layer 23d by a distance of 0.1 times the average thickness D of the dielectric layer 22. The interface between the dielectric layer 22 and the internal electrode layer 23d is considered to be substantially along the line segment Ed.
[0040] The grain size Tm is the grain size of the large ceramic grains 220a and the small ceramic grains 220b present on the center line Lm. The distribution of the grain size Tm along the center line Lm has two peaks as described below.
[0041] Fig. 6 is a diagram showing an example of the distribution of particle diameters Tm of the large diameter ceramic particles 220a and the small diameter ceramic particles 220b present on the center line Lm. In Fig. 6, the horizontal axis indicates the particle diameters Tm (nm) of the large diameter ceramic particles 220a and the small diameter ceramic particles 220b, and the vertical axis indicates the content (%) in the cross section of the dielectric layer 22.
[0042] The distribution of the particle size Tm has two peaks. One peak corresponds to the particle size k of the small ceramic particles 220b that are most distributed on the center line Lm, and the other peak corresponds to the particle size j of the large ceramic particles 220a that are most distributed on the center line Lm. When the particle size k of the small ceramic particles 220b is one third or less of the particle size j of the large ceramic particles 220a (i.e., k≦j / 3), the small ceramic particles 220b can effectively fill the gaps between the large ceramic particles 220a, and the unevenness of the surface of the dielectric layer 22 can be reduced and suitably smoothed.
[0043] In addition, when k≦j / 3 is satisfied, if the large-diameter ceramic particles 220a are in contact with at least one of the internal electrode layers 23u, 23d, the finer small-diameter ceramic particles 220b are distributed more on the center line Lm than when k>j / 3 is satisfied, and the gaps around the large-diameter ceramic particles 220a in contact with the internal electrode layers 23u, 23d can be sufficiently filled, which is preferable. This effectively reduces the unevenness of the surface of the dielectric layer 22, and suppresses layer destruction due to contact between the internal electrode layers 23u, 23d and the large-diameter ceramic particles 220a.
[0044] 5 again, in the cross section of the dielectric layer 22, the maximum particle size of the large ceramic particles 220a and the small ceramic particles 220b distributed on the center line Lm in the direction of extension of the center line Lm is Ra, and the maximum particle size of the large ceramic particles 220a and the small ceramic particles 220b distributed on the upper end line Lu and the lower end line Ld in the direction of extension of the upper end line Lu and the lower end line Ld is Rb. In this case, when k≦j / 3 is satisfied, if 0.1≦Rb / Ra≦0.8 is satisfied, finer small ceramic particles 220b are distributed more on the center line Lm than when k>j / 3 is satisfied, and finer small ceramic particles 220b are also distributed on the upper end line Lu and the lower end line Ld on the internal electrode layers 23u and 23d side, which is preferable. This makes it possible to effectively reduce and smooth the unevenness of the surface of the dielectric layer 22.
[0045] (Manufacturing process of multilayer ceramic capacitors) 7 is a flow chart showing an example of a manufacturing process for the multilayer ceramic capacitor 1. This manufacturing process is an example of a method for manufacturing a multilayer ceramic electronic component.
[0046] 8 is a cross-sectional view showing the process from green sheet formation step St1 to lamination and pressure bonding step St3. FIG 8 shows a cross section of the fired laminate 2 along the lamination direction and the length direction.
[0047] (Green sheet formation process) First, a green sheet forming process St1 is performed. As shown by the symbol P in Fig. 8, in the green sheet forming process St1, a slurry containing large-diameter ceramic powder 70a and small-diameter ceramic powder 70b having different particle sizes is applied onto a base material (not shown) to form green sheets 7a and 7b.
[0048] The slurry is obtained by wet mixing a dielectric material obtained by adding various additive compounds (such as sintering aids) to the large-diameter ceramic powder 70a and the small-diameter ceramic powder 70b, a binder such as polyvinyl butyral (PVB) resin, an organic solvent such as ethanol or toluene, and a plasticizer. The slurry is used to coat the green sheets 7a and 7b on a substrate by, for example, a die coater method or a doctor blade method, and then dried. The substrate is, for example, a PET (polyethylene terephthalate) film.
[0049] The average particle size of the small-diameter ceramic powder 70b is 0.25 times or less than the maximum particle size of the large-diameter ceramic powder 70a. The slurry is applied so that the average thickness Dt of the green sheets 7a, 7b is less than twice the average particle size of the large-diameter ceramic powder 70a. Therefore, one large-diameter ceramic powder 70a exists in the thickness direction of the green sheet 7a, and many small-diameter ceramic powders 70b exist around the large-diameter ceramic powder 70a.
[0050] In addition, as additive compounds for the large diameter ceramic powder 70a and the small diameter ceramic powder 70b, oxides of Mg (magnesium), Mn (manganese), V (vanadium), Cr (chromium), rare earth elements (Y (yttrium), Sm (samarium), Eu (europium), Gd (gadolinium), Tb (terbium), Dy (dysprosium), Ho (holmium), Er (erbium), Tm (thulium) and Yb (ytterbium)), as well as oxides or glasses of Co (cobalt), Ni, Li (lithium), B (boron), Na (sodium), K (potassium) and Si (silicon) are used.
[0051] (Internal electrode pattern formation process) Next, the internal electrode pattern forming process St2 is performed. In the internal electrode pattern forming process St2, the internal electrode patterns 6a and 6b are formed by applying conductive paste onto the green sheets 7a and 7b, respectively. The internal electrode pattern 6a becomes the internal electrode layer 23 after firing. The internal electrode patterns 6a and 6b are shifted from each other by half a pitch in the X direction.
[0052] In the internal electrode pattern forming process St2, a metal conductive paste for forming internal electrodes containing an organic binder is printed on the green sheet 7a by gravure printing or the like to form a plurality of internal electrode patterns 6a spaced apart from one another. Dielectric particles are added to the conductive paste as a co-material. The internal electrode patterns 6a may be formed by a vacuum deposition method such as sputtering, without being limited to printing.
[0053] (Lamination and bonding process) Next, a lamination and pressure bonding step St3 is performed. In the lamination and pressure bonding step St3, a plurality of green sheets 7a, 7b are alternately laminated and pressure bonded.
[0054] The green sheets 7a and 7b are sandwiched and pressed from above and below in the stacking direction by other green sheets 7c and 7d that will become cover layers 20 and 21 after firing. An internal electrode pattern 6b is formed on the surface of the bottommost green sheet 7d by the same method as in the internal electrode pattern forming step St2. Examples of pressing means include, but are not limited to, a hydrostatic press.
[0055] (cutting process) Next, a cutting step St4 is performed. In the cutting step St4, the pressed green sheets 7a-7d are cut, for example, by a blade along a plurality of cutting lines LW extending lengthwise and widthwise at regular intervals. As a result, the green sheets 7a-7d are divided into a plurality of pre-fired laminates 2. FIG. 8 shows the cutting lines LW extending along the width direction of the laminate 2. Ends of the internal electrode patterns 6a, 6b are exposed on the end faces 2A, 2B, which are the cut surfaces of the laminate 2.
[0056] (Firing process) Next, a firing step St5 is performed. In the firing step St5, the laminate 2 before firing is subjected to a binder removal process in an N2 atmosphere at 250 to 500°C, and then fired at a firing temperature of 1200°C or higher for about 1 hour in a reducing atmosphere with an oxygen partial pressure of 0.003 (Pa), thereby sintering each particle in the laminate 2. As a result, in the laminate 2, the green sheets 7a to 7d become the dielectric layer 22 and the cover layers 20 and 21, and the internal electrode patterns 6a and 6b become the internal electrode layer 23.
[0057] By the firing step St5, in the green sheets 7a and 7b, the large diameter ceramic powder 70a grows into large diameter ceramic particles 220a, and the small diameter ceramic powder 70b grows into small diameter ceramic particles 220b. As a result, the above-mentioned fine structure of the dielectric layer 22 is obtained.
[0058] (External electrode formation process) Next, an external electrode forming step St6 is performed. In the external electrode forming step St6, for example, a conductive paste containing metal powder, glass frit, binder, and solvent is applied to each end face 2A, 2B, upper face 2C, lower face 2D, and each side face 2E, 2F of the laminate 2. After the conductive paste is applied, it is dried to form the external electrodes 3a, 3b. The binder and the solvent are evaporated by baking. Examples of the method for applying the conductive paste include a sputtering method and a dipping method. The base electrode layer of the external electrodes 3a, 3b may be formed before the above-mentioned firing step St5 and fired simultaneously with the laminate 2. In this manner, the multilayer ceramic capacitor 1 is manufactured.
[0059] In the above manufacturing process, it is preferable that the small diameter ceramic powder 70b has an average particle size that is 0.2 times or less than the average particle size of the large diameter ceramic powder 70a, because this can further increase the difference in particle size between the large diameter ceramic particles 220a and the small diameter ceramic particles 220b after firing.
[0060] In the above manufacturing process, the slurry for forming the green sheets 7a, 7b may contain 4 to 8 times as many small diameter ceramic powder particles 70b as the large diameter ceramic powder particles 70a, thereby ensuring a sufficient number of small diameter ceramic powder particles 70b to fill the gaps around the large diameter ceramic powder particles 70a.
[0061] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to such specific embodiments, and various modifications and variations are possible within the scope of the gist of the present invention described in the claims. [Explanation of symbols]
[0062] 1. Multilayer ceramic capacitors 2. Laminate 3a,3b External electrode 6a, 6b Internal electrode pattern 7a~7d Green sheets 22 Dielectric layer 23,23u,23d Internal electrode layer 70a Large diameter ceramic powder 70b Small diameter ceramic powder 220a Large ceramic particles 220b Small ceramic particles
Claims
1. A laminate in which dielectric layers and internal electrode layers are alternately laminated, the dielectric layer includes a plurality of large ceramic particles having a diameter greater than half the average thickness of the dielectric layer, and a greater number of small ceramic particles than the large ceramic particles; A multilayer ceramic electronic component, characterized in that the particle size of the small-diameter ceramic particles is 0.25 times or less the maximum particle size of the large-diameter ceramic particles.
2. 2. The multilayer ceramic electronic component according to claim 1, wherein the diameter of the small ceramic particles is 0.2 times or less the maximum diameter of the large ceramic particles.
3. 3. The multilayer ceramic electronic component according to claim 1, wherein in a cross section of the dielectric layer along the stacking direction of the laminate, the particle size of the small-diameter ceramic particles that is most abundant on a line that divides the dielectric layer into two at approximately the center in the stacking direction is one-third or less of the particle size of the large-diameter ceramic particles that is most abundant on the line.
4. 4. The multilayer ceramic electronic component according to claim 3, wherein the large-diameter ceramic grains are in contact with the internal electrode layers.
5. In the cross section, the maximum particle size of the large-diameter ceramic particles and the small-diameter ceramic particles distributed on a line dividing the dielectric layer in two at approximately the center in the stacking direction is defined as Ra, and the maximum particle size of the large-diameter ceramic particles and the small-diameter ceramic particles distributed on a line dividing the dielectric layer in two at a position away from the interface with the internal electrode layer in the stacking direction by a distance of 0.1 times the average thickness of the dielectric layer is defined as Rb. 0.1≦Rb / Ra≦0.8 4. The multilayer ceramic electronic component according to claim 3, wherein the following is satisfied.
6. 3. The multilayer ceramic electronic component according to claim 1, wherein the dielectric layers have an average thickness of 0.2 to 0.4 μm.
7. 7. The multilayer ceramic electronic component according to claim 6, wherein a ratio of an average thickness of said internal electrode layers to an average thickness of said dielectric layers is greater than 0.5 and smaller than 1.
0.
8. forming a green sheet from a slurry containing a large diameter ceramic powder and a small diameter ceramic powder having an average particle size that is 0.25 times or less than the maximum particle size of the large diameter ceramic powder; forming a first internal electrode pattern on the green sheet; stacking and pressing a plurality of the green sheets; A step of dividing the plurality of pressed green sheets into a plurality of laminates along a lamination direction; and firing the laminate. a step of forming a green sheet having a thickness less than twice the average particle size of the large-diameter ceramic powder;
9. 9. The method for producing a multilayer ceramic electronic component according to claim 8, wherein the small-diameter ceramic powder has an average particle size that is 0.2 times or less the average particle size of the large-diameter ceramic powder.
10. 10. The method for producing a multilayer ceramic electronic component according to claim 8, wherein the slurry contains 4 to 8 times as many particles of the small diameter ceramic powder as the large diameter ceramic powder.
Citation Information
Patent Citations
Monolithic ceramic capacitor and method of manufacturing the same
JP2002305124A